The legal regime of the maritime zones around Svalbard: An analysis in light of recent developments in international law - Stikbakke, Øystein Røhnebæk (2021)
The topic of this thesis is the legal regime of the maritime zones around the archipelago of Svalbard under international law. Three questions are discussed in the thesis: First, whether Spitsbergen, Bear Island and Hope Island of the Svalbard archipelago are entitled to an Exclusive Economic Zone (EEZ) and continental shelf under Art. 121(3) of UNCLOS. Second, whether other States are precluded from challenging the maritime zones already established around Svalbard under the doctrines of estoppel and acquiescence. Third, whether the equal access rights of Art. 2 and 3 of the Svalbard Treaty are applicable to the Fisheries Protection Zone (FPZ) and continental shelf of Svalbard under Art. 311 of UNCLOS.